Influence of cognitive impairment on the freezing of gait in non demented people with Parkinson’s disease - Cancela, José M.; Nascimento, Carla M. [UNESP]; Varela, Silvia; Seijo-Martínez, Manuel; Lorenzo-López, Laura; Millán-Calenti, José C.; Domínguez-Vivero, Clara; Ayán, Carlos (IMR Press, 2018)
Introduction. Freezing of gait (FOG) is a motor disturbance usually appearing in advanced Parkinson’s disease (PD). Cognitive and executive function seems to play an important role in this phenomenon. Aim. To investigate if cognitive and kinematic parameters correlate with FOG in PD patients without dementia. Patients and methods. We conducted an observational cross-sectional study. Participants were classified in two groups: freezers and non-freezers. Clinical information was obtained by Hoehn & Yahr scale, Unified Parkinson’s Disease Rating Scale and balance test of Short Physical Performance Battery. Cognitive function was evaluated using Minimental Examination and the Fuld Object Memory Evaluation; executive function was assessed with the Frontal Assessment Battery test. Battery kinematic parameters were assessed by means of gait speed, cadence, stride length and stride time. Results. Twenty-five participants with PD without dementia completed the evaluation. Statistical significant differences between freezers and non-freezers were found in global cognition (p = 0.02), memory (p = 0.04), executive function (p = 0.04), cadence (p = 0.02), stride length (p = 0.04) and stride time (p = 0.01). Conclusion. Cognitive parameters may have an important contribution to the manifestation of freezing of gait in PD. These results may have important clinical implications for developing future non-pharmacological and cognitive interventions strategies targeted to PD patients with FOG.
Influencia del deterioro cognitivo en la congelación de la marcha en pacientes con enfermedad de Parkinson sin demencia
Keywords: Cognition; Gait; Motor disturbance; Older people; Parkinson’s disease